2012
DOI: 10.1007/s11010-012-1224-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of HMGA2 transcription factor binding sites by ChIP on chip in gastric carcinoma cells

Abstract: High mobility group protein A2 (HMGA2) is an architectural transcription factor that plays an important role in development and progression of malignant neoplasias. Recently, some studies reported that HMGA2 is also implicated in epithelial-mesenchymal transitions (EMT) and cancer stem cells. But the underlying mechanisms of these conditions are poorly understood. Therefore, we established an EMT model of gastric carcinoma cells by overexpressing HMGA2 in vitro, then global mapping of HMGA2 potential transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Although we did not examine whether HMGA2 directly binds to HAT promoters to regulate expression, HMGA2, by acting as a global chromatin switch, has been shown to regulate >1,000 genes [31]. Some of these genes are regulated by HMGA2 by directly binding to the promoter sequences.…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not examine whether HMGA2 directly binds to HAT promoters to regulate expression, HMGA2, by acting as a global chromatin switch, has been shown to regulate >1,000 genes [31]. Some of these genes are regulated by HMGA2 by directly binding to the promoter sequences.…”
Section: Discussionmentioning
confidence: 98%
“…It is reasonable to propose that HMGA2 promotes VM formation in GC by regulating VE-cadherin. A computational analysis predicted that HMGA2 can target the promoter of Twist1 39 . It is known that Twist1 opens nuclear membrane pores with the help of an accessory protein and enters the nucleus to regulate the transcription of downstream genes that are involved in the process of VM 40 , and we have previously reported that Twist1 facilitates VM by modulating the promoter of VE-cadherin in hepatocellular carcinoma 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HMGA2 overexpression can partially reverse the repressive effects of JQ1 on c-MYC and/or FOSL1 . Given that HMGA2 can act as a global chromatin switch (47), it is also possible that the ability of HMGA2 to counteract JQ1 may be through its effect on global changes in gene expression rather than modulation of c-MYC and/or FOSL1. Indeed, it has been shown that HMGA2 can regulate > 1,000 genes, either directly by binding to promoter sequences or indirectly through activation of signaling pathways (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Given that HMGA2 can act as a global chromatin switch (47), it is also possible that the ability of HMGA2 to counteract JQ1 may be through its effect on global changes in gene expression rather than modulation of c-MYC and/or FOSL1. Indeed, it has been shown that HMGA2 can regulate > 1,000 genes, either directly by binding to promoter sequences or indirectly through activation of signaling pathways (47, 48). Although it is beyond the scope of this study, we plan in future studies to examine the effect of HMGA2 overexpression on changes in global gene expression following JQ1 treatment.…”
Section: Discussionmentioning
confidence: 99%